Ruptured giant lateral thoracic meningocele associated with intracranial hypotension syndrome in neurofibromatosis type 1: case report with long-term follow-up - Li, Wenfu; Zhou, Hui (Frontiers in Oncology, 2025)
Lateral thoracic meningocele is a rare clinical entity typically associated with neurofibromatosis type 1 (NF1), which can progressively enlarge under the cerebrospinal fluid (CSF) pressure. Despite its rarity, these lesions may rupture or be associated with intracranial hypotension syndrome (IHS). We herein describe a 50-year-old woman presenting with a 2-year history of dyspnea, positional headaches, and dizziness. Imaging revealed a giant lateral thoracic meningocele with right-sided pleural effusion. Following thoracentesis with evacuation of 480 ml effusion (later confirmed as CSF), her headache intensified markedly; subsequent brain MRI demonstrated characteristic features of IHS. Surgical excision of the meningocele was performed, and the patient experienced a favorable recovery, with discharge on postoperative day 22. This case underscores critical clinical insights: NF1-associated giant lateral thoracic meningoceles may manifest respiratory symptoms alongside severe complications, including rupture and IHS. Crucially, procedures such as thoracentesis require extreme caution, as they risk exacerbating CSF leakage and may precipitate life-threatening cerebellar tonsillar herniation.